Marketing pattern of Murrah buffaloes among Dairy Farmers affected by Integrated Murrah Development Scheme of Haryana - Jadoun, Yogendra Singh; Jha, Sujit Kumar; Bhaduria, Pragya; Kale, Rajiv Baliram (Indian Journal of Dairy Science, 2014)
Haryana is proud to be the home-tract of one of the best buffalo breeds of the world i.e. ’Murrah’ buffalo. There is a great demand of this high yielding elite breed not only from within but outside the country. The present study investigates the existing status of Murrah buffalo marketing pattern in Haryana. It was found that majority of the beneficiaries (78.75%) and non-beneficiaries (65.63%) decided to purchase whereas, 75.00% beneficiaries and 65.63% non-beneficiaries decided to sell the buffaloes by themselves. The preferred place of marketing of buffalo was village itself. Whereas preferred season of sell or purchase was winter. Dairy characteristic mainly milk yield considered as major criteria of selection of Murrah buffalo owner during purchase. Majority of the beneficiaries and non-beneficiaries were interested in recording 2-3 milking before purchasing the Murrah buffaloes.Â It was also evident that the respondents were practicing the various improved identification and selection practices during sale andÂ purchase to a greater extent, but there is a need to emphasize upon the buffalo keepers to veterinary check-up practices to ensure the sale and purchase of healthy buffaloes.